Comparison of frequency of coach replacement during the championship in the high professional soccer league between two European countries - Mitrotasios, M.; Siskos, C.; Zelenitsas, C. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The phenomenon of coach replacement during the championship proves to be the greatest problem that characterizes this profession [1, 2, 3, 4]. The aim of this study was to examine and to compare the frequency of coach replacement during the championship in the highest professional soccer League between two European Countries (Spain and Greece). Methods All coach replacements (77) of the teams in the professional highest Division (N=178) which took place during the championship from 2000/1 to 2004/5 were recorded. 78 teams of the ones referred to above (43.8%) belonged to 1st professional Division (super league) of Greece and 100 teams (56.2%) belonged to Primiera Division of Spain. During the statistical analysis, descriptive statistics were used, while for the independent variables the x2-test was applied. Variables regarding (a) the frequency of coach replacement and (b) the performance of the teams` ratings in the table position were analyzed. Results The results indicated that a high percentage of the teams (43.3%) during the examined periods replaced a coach. In fact, 42.9% (N=33) out of the 77 teams, which implemented the replacement, used more than two coaches for the same season. However, the frequency of replacements was significantly higher (x2=9.784, p<.01) in 1st professional Division of Greece (56.4%) compared to Primiera Division of Spain (33.0%). No significant improvement of the situation from one soccer season to the next was noted for both countries (p= 0.46). As far as the time period where most coach replacement took place, a considerable difference between Greece and Spain was noted (x2=5.898, p < .01). In 1st professional Division of Greece, most coach replacement occurred during the first round (72.7%), while in Primiera Division the replacements occurred during the second round (54,5%). The rating of the teams in the final score board (at the end of the season), which effected the replacement of coaches, improved, with no significant differences between the two countries (p= 0.69), only for 42.9% of the teams, while 57,1% either remained in the same position or in an even lower one. Discussion The results of this research depict the insecurity as well as the uncertainty which characterizes the profession of a soccer coach, due to the high frequency of coach replacements which takes place in the teams during the soccer season. Also, the significant recorded differences between the two countries regarding coach replacement, manifest the difference of professionalism between the teams 1st professional Division of Greece and Primiera Division of Spain. Apart from that, the results show that the coach replacement during the championship carries a high risk, because the probabilities of improvement in the course of the team are fewer, since for the higher percentage of the teams the rating at the end of the soccer season was at the same or even lower levels.